Enhancing the thermal insulation properties of polymer-derived SiCN(O) ceramic aerogels with a polysilazane-precursor design. Issue 10 (15th May 2023) - Wang, Wei; Pang, Le; Jiang, Ming; Zhu, Yaping; Wang, Fan; Sun, Jingwen; Qi, Huimin
Abstract: In this study, we investigated the tunable porous structure of SiCN(O)-derived ceramic aerogels by changing the molecular structure of the polysilazanes from linear to branched. We also studied the effect of molecular structure on the thermal insulation properties of ceramic aerogels. As the percentage of branched molecular structure in the polysilazane precursor increased, the internal microscopic pore structure of the aerogels changed from macroporous to mesoporous. The specific surface areas and pore volumes of the ceramic aerogels prepared with different precursors increased after pyrolysis at 1000 °C, ranging from 3.7 to 255.9 m 2 /g and 0.01–0.36 cm 3 /g, respectively. The corresponding thermal conductivities increased slightly as the aerogels contracted after pyrolysis. The low thermal conductivity (0.046 W/(m·K) at minimum) can be attributed to the decrease in pore size caused by adjusting the precursor structure, which limits the thermal conduction of gas in the porous aerogel materials.